A Case Study on Learning Proofs of the Pythagorean Theorem through Diagramming: Based on the Châteletean Perspective - Jeong-Won Noh; Kyeong-Hwa Lee; Sung-Jae Moon (Korea Society of Educational Studies in Mathematics, 2021)
This study aims to reveal how diagramming in the everyday mathematics classroom supports students' mathematical learning, based on the Châteletean perspective. To this end, we analyzed the diagramming of two 9th grade students who participated in the task of proving the Pythagorean theorem through diagrams in a geometry lesson. In particular, we focused on the epistemic distance as well as the material directness between the students and the diagrams. As a result, the students discovered mathematical ideas while they engaged in direct or indirect diagramming; they actualized virtual mathematical objects and relationships that were not visible in the given diagrams. During diagramming, the epistemic distance between the students and the diagrams was also dynamically changing. The findings suggest that diagramming in mathematics classrooms is not just a static representational activity, but an indeterminate and mobile engagement, which materially interacts with diagrams at varying degrees of epistemic distance.